SEEKING COMMON GROUND: THE ENGLISH DISCOURSE MARKERS OKAY - Mišković Luković, Mirjana (Наслеђе, 2015)
This paper studies the cognitive role of the English discourse marker okay in utterance interpretation. It argues that in analysing data it is important to make two crucial distinctions. The first distinction is semantic about the type of meaning encoded by a linguistic item – conceptual or procedural. The second is a pragmatic distinction between explicitly and implicitly communicated meanings. Relying on the notions of common ground and mutual manifestness (of assumptions), I put forward a univocal semantic analysis of okay as a procedural indicator of a particular contextual assumption. The analysis is couched within the relevance-theoretic framework and based on data from formal and informal types of discourse.